DESIGN OF ULTRASONIC NONDESTRUCTIVE TESTING SYSTEM WITH PULSE ECHO METHOD AND THE EXPERIMENT ON STEEL SPECIMENS AS RAIL MODEL - Rodik Wijaya, Ahmad
The acceleration of the development of railway facilities in Indonesia must be supported by increased attention to safety aspects, including by monitoring the quality of railroad infrastructure. Inspection of the railroad other than visually, is done by non-destructive tests to evaluate the internal conditions of the railroad tracks which utilize ultrasonic waves. Therefore, a discontinuity testing system for railroad tracks will be developed by designing test specimens from the same steel material. The ultrasonic measurement system consists of an ultrasonic pulse generating device (pulser), an ultrasonic transducer, a digital oscilloscope, and a time of flight (TOF) signal processing program. Test object as a modelling of rail defects consists of a standard calibration block and test specimens that has designed defects in planar and cylindrical shape. The ultrasonic method used is pulse-echo with a single element transducer. The pulser specifically consists of DC voltage amplifier blocks and switching circuits which are controlled by the Arduino microcontroller. The pulser signal output has an average voltage of 178.08 V, rise time of 108.33 ns, and decay time of 3200 ns. The results of the longitudinal wave velocity measurements in the calibration block produce CL 5912.16 m / s. The measurement of test object with parallel planar shape defects obtained the mean absolute percentage error (MAPE) on block calibration object 0.14%, and on test specimen 2 0.22%. While for planar defects at an angle of 5° and 10°, obtained MAPE 0.56%. In test objects with cylindrical shape defects, MAPE test specimens 2 were obtained (diameter 10 mm) 0.28%, calibration block (diameter 3 mm) 0.86%, and test specimen 1 (diameter 1 mm) 1.36 %.